TEOLOGI PENDIDIKAN DALAM DE CIVITATE DEI:: IMPLIKASI BAGI KELUARGA KRISTEN MODERN - Puling, Harun; Selan, Ongkilion (Jurnal Teologi RAI, 2025)
This article examines the theology of education in Augustine’s De Civitate Dei and its implications for the modern Christian family. The study highlights the role of Christian education as a foundation for shaping children’s character and faith amidst contemporary challenges such as secularization, globalization, and shifting social values. The purpose of this research is to analyze Augustine’s educational principles, explore their application within modern families, and formulate contextual and effective faith formation strategies. The method employed is library research with a qualitativedescriptive approach, combining historical-theological analysis and practical reflection. The findings indicate that Christian education, according to Augustine, emphasizes a balance between spiritual and moral formation, parental exemplarity, and the integration of divine values in daily life. Practical implications include establishing routines of prayer and worship together, strengthening family communication based on biblical values, and instilling spiritual discipline from an early age. Augustine’s principles in De Civitate Dei provide a strategic foundation for modern Christian families to navigate contemporary challenges while maintaining authentic faith identity.